Elaboração de um plano de manutenção preventiva na rede de ar comprimido e compressores na empresa Ninfa Indústria de Alimentos Ltda. - Piúna, Jéssica Morais (2014)
This project aims to implement a preventive maintenance plan in the compressed air system and compressor company Nymph Ltda. Food Industry. The completion of the work was done through a computerized system of free access, to assist in proper planning of interventions with predetermined periods of time. The company does not have such maintenance, generating the idea of implementing the preventive maintenance plan. With such a deployment becomes possible the coding of equipment, inventory control that generates cost savings as a result. The implementation relies on the aid of theoretical references that optimize a preventive system in the industry to introduce quality in services and products. The quality factor has a positive approach in influencing organizational performance. The computerized system implemented is able to be changed to a plan that does not have the restrictions found in the base model, and further improve the performance of the company regarding how interventions are performed.